Staggered Magnetic Nanowire Devices for Effective Domain-Wall Pinning in Racetrack Memory - Al Bahri, M.; Borie, B.; Jin, T. L.; Sbiaa, Rachid; Klaui, M.; Piramanayagam, S. N. (Physical Review Applied, 2019)
Domain-wall memory devices, in which the information is stored in nanowires, are expected to replace hard disk drives. A problem that remains to be solved in domain-wall memory is to pin the domain walls in a controllable manner at the nanometer scale using simple fabrication. We demonstrate the possibility to stabilize domain walls by making staggered nanowires. Controllable domain-wall movement is exhibited in permalloy nanowires using magnetic fields where the pinning field is about 10 mT. The pinning field and stability of the domain walls can be increased by adjusting the offset dimensions of the staggered nanowires. Domain-wall velocities of about 200 m/s are computed for the experimentally used permalloy nanowires. Domain-wall velocities are found to be independent of pinning strength and stability, providing a way to tune the pinning without compromising domain-wall velocities.
CRIS-Team Scopus Importer:2023-03-27